2017
DOI: 10.1590/1806-9061-2016-0228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthetic Emulsifier and Natural Biosurfactant on Feed Process and Quality of Pelletized Feed in Broiler Diet

Abstract: A feed production trial was conducted to study the effect of synthetic emulsifier and natural biosurfactant the process and quality of pelletized broiler feed. A corn-soy based broiler diet was formulated with fixed ratio 2:1 of oil-to-water with two types of emulsifiers, namely glyceryl polyethylene glycol ricinoleate synthetic emulsifier and lysophosphatidylcholine natural biosurfactant. T1: Basal diet with no water and no emulsifier; T2: Basal diet with water and no emulsifier; T3: Basal diet with water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
3
0
2
Order By: Relevance
“…As an alternative low-cost option, dietary fat and oil can provide a reasonable level of energy in the diet. However, the quantity of fat and oil added to a diet should be restricted to no more than 5% because a higher fat and oil content could negatively impact both the feed manufacturing process and feed quality (1). According to previous studies (2,3), different types of fat influence the growth performance of fastgrowing broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative low-cost option, dietary fat and oil can provide a reasonable level of energy in the diet. However, the quantity of fat and oil added to a diet should be restricted to no more than 5% because a higher fat and oil content could negatively impact both the feed manufacturing process and feed quality (1). According to previous studies (2,3), different types of fat influence the growth performance of fastgrowing broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of emulsifier and lipase supplementation in diet on nutrient digestibility of the broiler chickens1,2,3 .…”
mentioning
confidence: 99%
“…In line with previous research (Groesbeck et al, 2008; Tavernari et al, 2013), the presence of glycerol in CFP (approximately 10%) which acts as emulsifier or surfactant can improve PDIT. Recently, Cheah et al (2017) revealed that the addition of synthetic glycerol (0.05% in the diet) as an emulsifier significantly enhances moisture content of discharged feed at a conditioner ( P < 0.0011), feed starch gelatinization ( P < 0.0001), and PDIT. Therefore, it seems that CFP possesses emulsifier properties compared to SO-based diets which reduce layer-barrier problem and probably leads to better starch gelatinization.…”
Section: Discussionmentioning
confidence: 99%
“…Дуже часто споживання корму недостатньо для задоволення потреби в поживних речовинах і це може негативно позначитися на масі й однорідності поросят після відлучення. Тому додавання високих рівнів жирів у раціони допомагає задовольнити потреби в живленні, щоб уникнути негативного енергетичного балансу (Cheah et al, 2017).…”
Section: вступunclassified
“…Допомагає це і в спекотних літніх умовах, оскільки жир ефективно метаболізується з відносно низьким виділенням тепла, а калорійні корми даватимуть необхідний ефект, коли спостерігається зниження апетиту. Аналогічна ситуація складається, у свиноматок у період лактації, коли тварини відчувають негативний енергетичний баланс (Cheah et al, 2017).…”
Section: вступunclassified